Event-triggered control via reset control systems framework. Issue 18 (2016) - Seuret, A.; Prieur, C.; Tarbouriech, S.; Zaccarian, L.
Abstract: This paper deals with a systematic way to design the event-triggered rules to stabilize a class of linear reset control systems. The event-triggering condition depends only on local information, that is it only uses the measured signals. The approach proposed combines a hybrid framework to describe the sampled-data system with Lyapunov-based techniques. Dwell-time dependent constructive conditions expressed through linear matrix inequalities (LMI) are proposed to design the event-triggered rule ensuring the asymptotic stability of the closed-loop system. The effectiveness of the approach is evaluated through an example borrowed from the literature.